Topical Use of Quercetin-Loaded Chitosan Nanoparticles Against Ultraviolet B Radiation - Nan, Wenhao; Ding, Li; Chen, Houjie; Khan, Fahim U.; Yu, Lu; Sui, Xinbing; Shi, Xiaojun (Frontiers in Pharmacology, 2018)
Ultraviolet radiation is a major risk factor for human skin damage, especially solar ultraviolet-B (UVB) which can induce inflammation, photoaging, and skin cancer. Quercetin (Qu), one of flavonoid family members, has showed protective effects against UVB radiation. However, its application for topical use is limited by low hydrophilicity and poor percutaneous absorption. Herein, we found that Qu, if entrapped into TPP-Chitosan nanoparticles (TCs), can be efficiently uptake by HaCaT cells and easily permeate through the epidermis layer, meanwhile display better stability and low cytotoxicity. We also found that Qu-loaded TCs (QTCs) could notably enhance the effect of Qu on inhibiting the NF-kB/COX-2 signaling pathway as well as ameliorating the skin edema caused by UVB radiation. Therefore, this study provided a method to get rid of Qu’s low hydrophilicity, enhance its percutaneous absorption and retention in the skin, and further improve its anti-UVB effect, and demonstrated that Qu-loaded chitosan nanoparticles can be used as the therapeutic agent for topical use against UVB radiation.